Primary cutaneous vs secondary cutaneous follicular lymphomas: A comparative study focused on BCL2, CD10, and t(14;18) expression. (26th December 2018) - Servitje, Octavio; Climent, Fina; Colomo, Lluis; Ruiz, Nuria; García‐Herrera, Adriana; Gallardo, Fernando; Mercadal, Santiago; Pomares, Helena; Muniesa, Cristina; Martin‐Callizo, Clara; Marcoval, Joaquim; Rovira, Roger; et al.
Abstract : Background: Primary cutaneous follicular center‐cell lymphoma (PCFCL) is one of the most common types of cutaneous B‐cell lymphoma. Differences in immunohistochemical expression of BCL2 and CD10 antigens along with the presence of t(14:18) translocation in neoplastic cells have been postulated as relevant clues in differentiating PCFCL from cutaneous lesions secondary to a systemic follicular lymphoma (SCFL). The aim of this study is to evaluate the significance and usefulness of these parameters in a large series of patients. Methods: Patients with PCFCL and SCFL diagnosed at three university hospitals in Barcelona, from 2000 to 2015 were reviewed. Clinical, histopathological, immunophenotypical, genetic, and outcome parameters were analyzed. Results: Eighty‐one cases (59 PCFCL and 22 SCFL) were included. There were no significant differences between PCFCL and SCFL cases regarding clinical presentation, site of involvement, or predominant type of skin lesions. Most patients in both groups showed positivity for BCL2 and CD10, but strong expression of BCL2 and CD10 was associated with SCFL cases. Although more frequent in SCFL, a small proportion of PCFCL cases also showed the t(14:18) on FISH analysis. Conclusion: The intensity of BCL2 expression was found to be the single most valuable clue in differentiating PCFCL from SCFL cases on histopathological grounds.